ESG rating disagreement and stock mispricing - Yu, Jiangzhi; Ma, Shenglin (Journal of Business Economics and Management, 2026)
Identifying the causes of stock mispricing is crucial for stabilizing capital markets. Utilizing panel data from Chinese A-share listed firms, this paper investigates the causal association between ESG rating disagreement and stock mispricing. We reveal that ESG rating disagreement significantly exacerbates stock mispricing. Further analysis shows that cross-shareholding investors, media attention and marketization weaken the relationship between ESG rating disagreement and stock mispricing. We also demonstrate that the influence of ESG rating disagreement on stock mispricing is more pronounced in state-owned enterprises, heavy pollution enterprises and enterprises with short-term institutional investor holdings. These findings help to provide some insights into ESG rating disagreement as a determinant influencing stock mispricing among emerging markets.